2013
DOI: 10.1002/ajpa.22370
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope ratio analysis of breastfeeding and weaning practices of children from medieval Fishergate House York, UK

Abstract: Rib collagen of 51 juveniles and 11 adult females from the late medieval Fishergate House cemetery site (York, UK) were analyzed using nitrogen and carbon stable isotope ratio analysis to determine the weaning age for this population and to reconstruct diet. The juveniles' ages ranged from fetal to 5-6 years, while the females were of reproductive age. Previous researchers suggested that the children from Fishergate House might have been weaned later than the medieval British norm of 2 years, based on a mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
47
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 42 publications
10
47
1
Order By: Relevance
“…Haydock et al (2013) targeted British BWPs in the late Anglo-Saxon (978-1040 cal AD) and compared the result with several previous isotopic studies on British BWPs; they found that the weaning ages become younger from the Iron Age to the 19th century. Their results of decreasing weaning ages are consistent with the newly reconstructed weaning ages of a population in medieval (10th to 16th centuries AD) Britain (Burt, 2013). Howcroft et al (2014) reconstructed infant feeding practices in a hunter-gatherer skeletal population from the Middle Neolithic Pitted Ware Culture (after 2750 BC), Sweden, and showed that the majority of subadults were breastfed until the third or fourth year of age.…”
Section: Applications Studied Tissuessupporting
confidence: 66%
“…Haydock et al (2013) targeted British BWPs in the late Anglo-Saxon (978-1040 cal AD) and compared the result with several previous isotopic studies on British BWPs; they found that the weaning ages become younger from the Iron Age to the 19th century. Their results of decreasing weaning ages are consistent with the newly reconstructed weaning ages of a population in medieval (10th to 16th centuries AD) Britain (Burt, 2013). Howcroft et al (2014) reconstructed infant feeding practices in a hunter-gatherer skeletal population from the Middle Neolithic Pitted Ware Culture (after 2750 BC), Sweden, and showed that the majority of subadults were breastfed until the third or fourth year of age.…”
Section: Applications Studied Tissuessupporting
confidence: 66%
“…The initial osteology report from Fishergate House indicated a high mortality rate at 4e6 years, which does not match the weaning period (2 years) found in contemporaneous British communities (Burt, 2013;Fuller et al, 2003Fuller et al, , 2006bHolst, 2005;Jay et al, 2008;Mays et al, 2002;Richards et al, 2002). The weaned child diet at Fishergate House reconstructed using a small sample of ribs is unusual as it is not the same as that of the adult females studied (Burt, 2013).…”
Section: Introductionmentioning
confidence: 88%
“…The weaned child diet at Fishergate House reconstructed using a small sample of ribs is unusual as it is not the same as that of the adult females studied (Burt, 2013). At Fishergate House, weaned children appear to have a diet rich in marine protein and pig much like high socioeconomic individuals in a neighboring York suburb rather than a grain based diet as seen with their poor contemporaries (Burt, 2013;Fuller et al, 2003;Mays et al, 2002;Richards, 2007a, 2007b;Richards et al, 2002).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This result derives from a higher trophic level due to breastfeeding. Nursing babies consume mother's milk which is enriched with 15 N (Bourbou et al 2013;Burt 2013;Fuller et al 2006;Katzenberg 2008;Katzenberg et al 1996). In this study, only one child (A50) aged 3 to 5 years could be analysed for stable isotope ratios.…”
mentioning
confidence: 99%